CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst as well as preparation method and application thereof
By combining CeO2 and ZnMn2O4 to form a Z-shaped heterojunction, the existing photocatalysts have solved the problem of high photocarrier recombination rate and insufficient hole oxidation capacity when degrading tannin acid, and achieved efficient and stable photocatalytic degradation effect .
Patent Information
- Application Number
- CN202410770979.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-14
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-06-14
AI Technical Summary
When degrading tannin acid, existing photocatalysts have problems such as high photocarrier recombination rate and insufficient hole oxidation capacity, resulting in low degradation efficiency.
By combining CeO2 and ZnMn2O4 to form a Z-type heterojunction, the visible light absorption capacity is enhanced, the recombination of photogenerated carriers in the photocatalytic reaction is suppressed, and the hole oxidation capacity is improved.
The efficient degradation of tannin acid was achieved, the photocatalytic degradation efficiency and reaction stability were significantly improved, the structure was stable after recycling, and the degradation rate was maintained at a high level.
Smart Images

Figure CN119425667A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalysis, and in particular relates to a CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst and a preparation method and application thereof. Background Art
[0002] In the hydrometallurgical zinc smelting process, germanium is a rare associated metal with high recovery value, which is enriched in zinc oxide dust. At present, adding excess tannic acid to the acid leaching solution of zinc oxide dust to precipitate germanium is the main means of recovering germanium in the zinc smelting process. However, a large amount of excess tannic acid returns to the leaching solution after liquid-solid separation, which increases the viscosity of the electrolyte and reduces the electrical efficiency. In severe cases, it will cause cathode zinc to dissolve back or even burn the plate. The industrial methods for removing tannic acid from the leaching solution generally have problems such as insufficient degradation, high operating costs, and easy secondary pollution. Photocatalysis, as a green and efficient method for degrading organic matter, is increasingly favored by researchers.
[0003] Traditional photocatalysts such as TiO2 and ZnO can only absorb high-energy photons due to their wide bandgap. They require high-power ultraviolet radiation when used, which increases production costs and limits their practical applications. ZnMn2O4, as a new type of spinel photocatalyst, has the advantages of visible light response, good photochemical stability and excellent catalytic activity. At the same time, ZnMn2O4 has low solubility in acidic environments, and the dissolved zinc and manganese ions will not cause secondary pollution to the leachate. However, the narrow bandgap and low valence band potential characteristics of ZnMn2O4 make the photogenerated carrier recombination rate high during the photoreaction process, and the hole oxidation capacity is insufficient, making it difficult to efficiently degrade tannic acid. Summary of the invention
[0004] In order to solve the technical problems and shortcomings in the prior art, the object of the present invention is to provide a photocatalyst that can efficiently degrade tannic acid.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] In a first aspect, the present invention provides a method for preparing a CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst, comprising the following steps:
[0007] (1) Preparation of ZnMn2O4:
[0008] Add zinc acetate (CH3COO)2Zn·2H2O and manganese acetate (CH3COO)2Mn·4H2O into ethanol-water solution and stir until completely dissolved to obtain solution A;
[0009] Add oxalic acid H2C2O4·2H2O to ethanol-water solution and stir until completely dissolved to obtain solution B;
[0010] The solution A is quickly poured into the solution B, heated and stirred to obtain a mixed solution, and after the mixed solution is cooled to room temperature, it is filtered, washed and dried to obtain a precursor A;
[0011] Precursor A is placed in a tube furnace for high-temperature calcination to obtain ZnMn2O4 in the form of long strips;
[0012] (2) Preparation of CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst:
[0013] The ZnMn2O4 obtained in step (1) is added to the cerium nitrate solution, and stirred thoroughly to be uniformly dispersed in the cerium nitrate solution; then 25% ammonia water is added dropwise, heated and stirred to obtain a precipitated mixture, and after the reaction, the precipitated mixture is cooled to room temperature, filtered, washed and dried to obtain a precursor B, and the precursor B is placed in a tubular furnace for high-temperature calcination to obtain a CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst.
[0014] Preferably, in step (1), the total metal ion concentration of zinc and manganese in the solution A is 0.02 to 0.16 mol / L.
[0015] Preferably, in step (1), the molar ratio of zinc acetate to manganese acetate is 1:2, and the molar ratio of oxalic acid to zinc acetate is 3-3.6:1.
[0016] Preferably, in step (1), the heating and stirring are performed at a heating temperature of 50 to 60° C., a stirring rate of 500 to 1000 r / min, and a stirring time of 2 to 2.5 h.
[0017] Preferably, in step (1), the volume ratio of ethanol to water in the ethanol-water solution is 9:1.
[0018] Preferably, in step (2), the concentration of the cerium nitrate solution is 3.0-7.5 mmol / L, the amount of ZnMn2O4 added is 1.25-2 g / L, and the volume ratio of the 25% ammonia water added to the cerium nitrate solution is 0.01-1:40.
[0019] Preferably, in step (2), the heating and stirring are performed at a heating temperature of 40 to 50° C., a stirring rate of 500 to 700 r / min, and a stirring time of 2 to 2.5 h.
[0020] Preferably, in step (1) and step (2), the precursor A and the precursor B are heated to 450-550° C. at a heating rate of 2-10° C. / min for calcination, and the calcination holding time is 2-2.5 h.
[0021] The heating rate, calcination temperature and calcination time of step (1) and step (2) are the same.
[0022] In a second aspect, the present invention provides a CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst material prepared by the aforementioned preparation method, wherein the mass ratio of CeO2 to ZnMn2O4 is 0.25 to 1:1.
[0023] In a third aspect, the present invention provides the use of the aforementioned CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst material in photocatalytic degradation of tannic acid.
[0024] The present invention forms a Z-type heterojunction by compounding CeO2 and ZnMn2O4 to enhance the absorption capacity of visible light, effectively inhibit the recombination of photogenerated carriers in the photocatalytic reaction and improve the hole oxidation capacity, and has high photocatalytic degradation efficiency and reaction stability for tannic acid under simulated solar illumination.
[0025] Compared with the prior art, the beneficial effects of the technical solution of the present invention at least include:
[0026] (1) The CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst prepared by the present invention using a simple wet chemical-pyrolysis method has excellent visible light response ability and photocatalytic activity, can efficiently degrade tannic acid, and has better photocatalytic degradation performance than pure CeO2 and ZnMn2O4.
[0027] (2) The CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst prepared by the present invention has good stability and recyclability, and its structure remains stable after being recycled twice ( Figure 1 ), after four cycles of use, the degradation rate of tannic acid can still be maintained at a high level of 65.2%.
[0028] (3) The CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst prepared by the present invention forms a Z-type heterojunction, which effectively separates active oxidative species with stronger oxidation and reduction abilities under the action of the interfacial electric field, inhibits the recombination of photogenerated electrons and holes, and improves the photocatalytic efficiency. It has good practical value and potential application prospects in removing tannic acid in zinc leachate. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 1 and 2 are X-ray diffraction diagrams, wherein (a) is the X-ray diffraction diagram of the samples prepared in Example 1 and Comparative Example 1; and (b) is the X-ray diffraction diagram of the sample prepared in Example 1 before degradation and after two cycles of degradation.
[0030] Figure 2These are field scanning electron microscope photos of CeO2 prepared in Comparative Example 1 and ZnMn2O4 and CeO2 / ZnMn2O4 prepared in Example 1; wherein, a: CeO2, b: ZnMn2O4, c: CeO2 / ZnMn2O4.
[0031] Figure 3 It is the UV-visible diffuse reflectance spectra of the samples prepared in Comparative Example 1 and Example 1.
[0032] Figure 4 The nitrogen adsorption-desorption curves and pore size distribution diagrams of the samples prepared in Comparative Example 1 and Example 1 are shown.
[0033] Figure 5 This is the curve of tannic acid concentration changing with time in the photocatalytic degradation reaction of each group of samples in the application example. DETAILED DESCRIPTION
[0034] The objectives, specific implementation methods and advantages of the present invention are described in detail below, but the present invention is not limited to the following description.
[0035] The present invention compounds CeO2 and ZnMn2O4 to construct a Z-type heterojunction, which accelerates the migration and separation of photogenerated carriers under the action of the interface electric field, produces active oxidative species with enhanced oxidation ability, and further improves the photocatalytic efficiency. This is of great significance to the application of CeO2 and ZnMn2O4 in the field of photocatalysis and the removal of tannic acid in zinc leachate.
[0036] The technical solution of the present invention is described below in conjunction with specific embodiments:
[0037] Comparative Example 1:
[0038] The preparation of pure CeO2 includes the following steps:
[0039] Add 100 mg of cerium nitrate to 40 mL of deionized water and stir until completely dissolved; then add 0.8 mL of 25% ammonia water dropwise, stir at 40°C and 700 r / min for 2 hours, cool to room temperature, collect the precipitate by filtration, wash it with deionized water and ethanol three times, and dry it in an oven at 60°C overnight; finally, put the obtained precursor into a tubular furnace, keep it at 450°C for 2 hours at a heating rate of 2°C / min, and finally obtain CeO2 monomer material.
[0040] Embodiment 1:
[0041] A CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst is prepared by the following preparation steps:
[0042] (1) Preparation of ZnMn2O4:
[0043] 0.220g zinc acetate (CH3COO)2Zn·2H2O and 0.490g manganese acetate (CH3COO)2Mn·4H2O were added to an ethanol-water solution (45mL+5mL), and the mixture was stirred until completely dissolved to obtain a solution A having a total zinc and manganese metal ion concentration of 0.02mol / L. Similarly, 0.378g oxalic acid H2C2O4·2H2O was added to an ethanol-water solution (90mL+10mL) and stirred until completely dissolved to obtain a solution B. Solution A was then quickly poured into solution B and stirred at 60°C and 1000r / min for 2h to obtain a mixed solution. After the mixed solution was cooled to room temperature, it was filtered, washed and dried to obtain a precursor sample. Finally, the dried precursor was placed in a tubular furnace for calcination, and kept at 450°C for 2h at a heating rate of 2°C / min to finally obtain ZnMn2O4 with a long strip morphology.
[0044] (2) Preparation of CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst:
[0045] 100 mg of cerium nitrate is added to 40 mL of deionized water and stirred until completely dissolved; then 60 mg of ZnMn2O4 obtained in step (1) is added to the above cerium nitrate solution and stirred thoroughly to make it uniformly dispersed in the cerium nitrate solution; then 0.8 mL of 25% ammonia water is added dropwise, stirred at 40°C and 700 r / min for 2 hours, cooled to room temperature, filtered and collected the mixed precipitate, washed with deionized water and ethanol three times, and dried in an oven at 60°C overnight; finally, the dried precursor is placed in a tubular furnace and kept at 450°C for 2 hours at a heating rate of 2°C / min to obtain a CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst.
[0046] The X-ray diffraction patterns of the samples obtained in Example 1 and Comparative Example 1 of the present invention are shown in detail. Figure 1 ,Depend on Figure 1 It can be seen that all diffraction peaks of pure CeO2 can match those of CeO2 (JCPD card number 34-0394), indicating that it has high purity and good crystallinity. For pure ZnMn2O4, all diffraction peaks correspond to ZnMn2O4 (JCPD card number 24-1133). The X-ray diffraction pattern of the CeO2 / ZnMn2O4 composite material contains all the characteristic peaks of CeO2 and ZnMn2O4. Compared with pure CeO2, the peak position of the CeO2 / ZnMn2O4 composite material is basically not shifted, indicating that the compound of CeO2 has no effect on the lattice of ZnMn2O4. At the same time, no other obvious impurity phases were observed, which means that the CeO2 / ZnMn2O4 composite material has a high degree of crystallinity.
[0047] The field scanning electron microscope photos of the samples obtained in Example 1 of the present invention and Comparative Example 1 are shown in detail. Figure 2 ,Depend on Figure 2-a, it can be seen that CeO2 presents an irregular block morphology with a diameter of about 10 to 20 μm. Figure 2 -b Zinc manganate ZnMn2O4 is in the shape of long strips with a diameter of about 300nm and a length between 4 and 5μm. Figure 2 -c, the CeO2 / ZnMn2O4 composite material maintains the bulk shape of CeO2 as a whole, and the surface is covered with short rod-shaped ZnMn2O4.
[0048] The UV-visible diffuse reflectance spectra of the samples prepared in Example 1 and Comparative Example 1 of the present invention are shown in detail. Figure 3 ,Depend on Figure 3 It can be seen that pure CeO2 shows strong absorption in the ultraviolet region near 300nm, while ZnMn2O4 has strong absorption capacity in the visible light spectrum range near 400nm. Compared with pure ZnMn2O4, the absorption edge of CeO2 / ZnMn2O4 composite material shows red shift, showing enhanced visible light response, which can be attributed to the synergistic effect of ZnMn2O4 and CeO2. The results show that CeO2 / ZnMn2O4 composite material exhibits a broadened light absorption range and enhanced visible light absorption capacity, which is beneficial to photocatalytic reaction.
[0049] The nitrogen adsorption and desorption curves of the samples prepared in Example 1 and Comparative Example 1 of the present invention are shown in detail in Figure 4 ,Depend on Figure 4 It can be seen that ZnMn2O4, CeO2 and CeO2 / ZnMn2O4 composite materials show H3 type adsorption hysteresis loop and IV type characteristic isotherm of mesoporous materials. The specific surface area of CeO2 / ZnMn2O4 composite materials (95.483 m 2 ·g -1 ) are greater than ZnMn2O4(62.550m 2 ·g -1 ) and CeO2(86.935m 2 ·g -1 In addition, the pore volume of CeO2 / ZnMn2O4 composite material is also the largest among the three, which is 0.242cm 3 ·g -1 The pore volumes of ZnMn2O4 and CeO2 are 0.180 and 0.197 cm 3 ·g -1The results show that compared with ZnMn2O4 and CeO2, CeO2 / ZnMn2O4 composites have larger specific surface area and pore volume, providing more active sites, shorter bulk diffusion length and broadened mass transfer channels for photocatalytic reactions, and are conducive to enhancing both adsorption performance and photocatalytic efficiency.
[0050] Embodiment 2:
[0051] A CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst, which is different from Example 1 in that the total metal ion concentration of zinc and manganese is controlled to be 0.04 mol / L, the water bath temperature is 50°C, the stirring rate is 500 r / min, the stirring time is 2.5 h, the calcination temperature is 500°C, the heating rate is 5°C / min, and the calcination holding time is 2.5 h, is prepared by the following preparation steps:
[0052] (1) Preparation of ZnMn2O4:
[0053] 0.440g zinc acetate (CH3COO)2Zn·2H2O and 0.980g manganese acetate (CH3COO)2Mn·4H2O were added to an ethanol-water solution (45mL+5mL), and the mixture was stirred until completely dissolved to obtain solution A. Similarly, 0.756g oxalic acid H2C2O4·2H2O was added to an ethanol-water solution (90mL+10mL), and the mixture was stirred until completely dissolved to obtain solution B. Solution A was then quickly poured into solution B and stirred at 50°C and 500r / min for 2.5h to obtain a mixed solution. After the mixed solution was cooled to room temperature, it was filtered, washed and dried to obtain a precursor sample. Finally, the dried precursor was placed in a tubular furnace for calcination, and kept at 500°C for 2.5h at a heating rate of 5°C / min to finally obtain ZnMn2O4 with a long strip morphology.
[0054] (2) Preparation of CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst:
[0055] 80 mg of cerium nitrate was added to 40 mL of deionized water and stirred until completely dissolved; then 70 mg of ZnMn2O4 obtained in step (1) was added to the above cerium nitrate solution and stirred thoroughly to make it uniformly dispersed in the cerium nitrate solution; then 0.6 mL of 25% ammonia water was added dropwise, stirred at 50° C. and 500 r / min for 2.5 h, cooled to room temperature, filtered and collected the mixed precipitate, washed with deionized water and ethanol three times, and dried in an oven at 60° C. overnight; finally, the dried precursor was placed in a tubular furnace, and kept warm at 500° C. for 2.5 h at a heating rate of 5° C. / min to obtain a CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst.
[0056] Embodiment 3:
[0057] A CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst, which is different from Example 1 in that the molar ratio of oxalic acid to zinc acetate is controlled to be 3.6, the concentration of cerium nitrate solution is 7.5 mmol / L, and the amount of ZnMn2O4 added is 1.25 g / L, and is prepared by the following preparation steps:
[0058] (1) Preparation of ZnMn2O4:
[0059] 0.220g zinc acetate (CH3COO)2Zn·2H2O and 0.490g manganese acetate (CH3COO)2Mn·4H2O were added to an ethanol-water solution (45mL+5mL), and the mixture was stirred until completely dissolved to obtain solution A. Similarly, 0.454g oxalic acid H2C2O4·2H2O was added to an ethanol-water solution (90mL+10mL), and the mixture was stirred until completely dissolved to obtain solution B. Solution A was then quickly poured into solution B, and the mixture was stirred at 60°C and 1000r / min for 2h to obtain a mixed solution. After the mixed solution was cooled to room temperature, it was filtered, washed and dried to obtain a precursor sample. Finally, the dried precursor was placed in a tubular furnace for calcination, and kept at 450°C for 2h at a heating rate of 2°C / min to finally obtain ZnMn2O4 with a long strip morphology.
[0060] (2) Preparation of CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst:
[0061] 130 mg of cerium nitrate was added to 40 mL of deionized water and stirred until completely dissolved; then 50 mg of ZnMn2O4 obtained in step (1) was added to the above cerium nitrate solution and stirred thoroughly to make it evenly dispersed in the cerium nitrate solution; then 1 mL of 25% ammonia water was added dropwise, stirred at 40°C and 700 r / min for 2 h, cooled to room temperature, filtered and collected the mixed precipitate, washed with deionized water and ethanol three times, and dried in an oven at 60°C overnight; finally, the dried precursor was placed in a tubular furnace and kept at 450°C for 2 h at a heating rate of 2°C / min to obtain a CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst.
[0062] Application examples:
[0063] The CeO2 prepared in Comparative Example 1, the ZnMn2O4 prepared in Example 1 and the CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst were used to catalytically degrade tannic acid under simulated solar illumination.
[0064] The specific operations are as follows:
[0065] (1) Control group: 50 mL of 200 mg·L -1The tannic acid solution was treated in the dark for 30 minutes and then irradiated under a xenon lamp for 150 minutes.
[0066] (2) CeO2 group: 20 mg of CeO2 photocatalyst prepared in Comparative Example 1 was weighed and added into a quartz test tube, and then 50 mL of 200 mg·L -1 The tannic acid solution was poured into a quartz test tube containing the catalyst, and then ultrasonically dispersed for 5 minutes and then dark treated for 30 minutes to allow the catalyst to reach adsorption equilibrium. Then the xenon lamp was turned on to carry out photocatalytic reaction under simulated sunlight. 2 mL of the reaction solution sample was taken every 30 minutes, and the solution was filtered with a 0.22 μm filter membrane and the absorbance was measured by colorimetric method to obtain the residual concentration of tannic acid and calculate the reduction rate.
[0067] (3) ZnMn2O4 group: 20 mg of the ZnMn2O4 photocatalyst prepared in Example 1 was weighed and added to a quartz test tube, and then 50 mL of 200 mg·L -1 The tannic acid solution was poured into a quartz test tube containing the catalyst, and then ultrasonically dispersed for 5 minutes and then dark treated for 30 minutes to allow the catalyst to reach adsorption equilibrium. Then the xenon lamp was turned on to carry out photocatalytic reaction under simulated sunlight. 2 mL of the reaction solution sample was taken every 30 minutes, and the solution was filtered with a 0.22 μm filter membrane and the absorbance was measured by colorimetric method to obtain the residual concentration of tannic acid and calculate the reduction rate.
[0068] (4) CeO2 / ZnMn2O4 group: 20 mg of CeO2 / ZnMn2O4 photocatalyst prepared in Examples 1-3 were weighed and added into a quartz test tube, and then 50 mL of 200 mg·L -1 The tannic acid solution was poured into a quartz test tube containing the catalyst, and then ultrasonically dispersed for 5 minutes and then dark treated for 30 minutes to allow the catalyst to reach adsorption equilibrium. Then the xenon lamp was turned on to carry out photocatalytic reaction under simulated sunlight. 2 mL of the reaction solution sample was taken every 30 minutes, and the solution was filtered with a 0.22 μm filter membrane and the absorbance was measured by colorimetric method to obtain the residual concentration of tannic acid and calculate the reduction rate.
[0069] Depend on Figure 5It can be seen that within 30 minutes of dark treatment, the adsorption rate of tannic acid by CeO2 / ZnMn2O4 composite materials prepared by Examples 1-3 is better than that of the control group, pure CeO2 group and ZnMn2O4 group, which is related to its larger specific surface area and pore volume. The photodegradation results show that in the presence of pure CeO2 and ZnMn2O4, 51.3% and 89.3% of tannic acid are decomposed within 150 minutes of illumination time, respectively, while the CeO2 / ZnMn2O4 composite material prepared by Example 1 can only photodegrade all tannic acid within 90 minutes, and the photocatalytic removal rate of tannic acid by CeO2 / ZnMn2O4 prepared by Examples 2 and 3 can reach 99.5% and 95.1% respectively within 150 minutes. The photocatalytic degradation efficiency of CeO2 / ZnMn2O4 composite materials is significantly improved because the Z-type heterojunction formed by CeO2 and ZnMn2O4 is conducive to the rapid transfer of photogenerated carriers, inhibits the combination of photogenerated electron-hole pairs, and generates active oxidative species with enhanced oxidation ability.
[0070] Table 1. Photodegradation rate of tannic acid by materials in each experimental group
[0071] Time (min) Comparison <![CDATA[ZnMn2O4]]> <![CDATA[CeO2]]> Example 1 Example 2 Example 3 -30(dark reaction) 0% 0% 0% 0% 0% 0% 0 0.1% 46.7% 35.9% 62.4% 75.9% 51.9% 30 0.4% 64.4% 40.7% 89.1% 94.3% 86.5% 60 0.6% 76.7% 46.8% 99.0% 97.8% 93.3% 90 0.7% 84.7% 48.0% 100.0% 98.0% 93.8% 120 0.8% 89.1% 50.1% 100.0% 98.8% 94.5% 150 0.9% 89.3% 51.3% 100.0% 99.5% 95.1%
[0072] The above examples only express several preferred implementations of the present invention, and the detailed description cannot be understood as limiting the scope of the present invention. Under the premise of not departing from the technical concept and characteristics of the present invention, all modifications and equivalent modifications made according to the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing a CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst, characterized in that: The following steps are involved: (1) Preparation of ZnMn2O4: Add zinc acetate (CH3COO)2Zn·2H2O and manganese acetate (CH3COO)2Mn·4H2O into ethanol-water solution and stir until completely dissolved to obtain solution A; Add oxalic acid H2C2O4·2H2O to ethanol-water solution and stir until completely dissolved to obtain solution B; The solution A is quickly poured into the solution B, heated and stirred to obtain a mixed solution, and after the mixed solution is cooled to room temperature, it is filtered, washed and dried to obtain a precursor A; The precursor A is calcined to obtain ZnMn2O4 with a long strip morphology; (2) Preparation of CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst: The ZnMn2O4 obtained in step (1) is added to the cerium nitrate solution, and stirred thoroughly to be evenly dispersed in the cerium nitrate solution; then 25% ammonia water is added dropwise, heated and stirred to obtain a precipitated mixture, and after the reaction, the precipitated mixture is cooled to room temperature, filtered, washed and dried to obtain a precursor B, and the precursor B is calcined to obtain a CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst.
2. The preparation method according to claim 1, characterized in that: In step (1), the total metal ion concentration in the solution A is 0.02 to 0.16 mol / L.
3. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of zinc acetate to manganese acetate is 1:2, and the molar ratio of oxalic acid to zinc acetate is 3-3.6:
1.
4. The preparation method according to claim 1, characterized in that: In step (1), the heating and stirring are performed at a temperature of 50 to 60° C., a stirring rate of 500 to 1000 r / min, and a stirring time of 2 to 2.5 h.
5. The preparation method according to claim 1, characterized in that: In step (1), the volume ratio of ethanol to water in the ethanol-water solution is 9:
1.
6. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the cerium nitrate solution is 3.0-7.5 mmol / L, the amount of ZnMn2O4 added is 1.25-2 g / L, and the volume ratio of the 25% ammonia water added to the cerium nitrate solution is 0.01-1:
40.
7. The preparation method according to claim 1, characterized in that: In step (2), the heating and stirring are performed at a temperature of 40 to 50° C., a stirring rate of 500 to 700 r / min, and a stirring time of 2 to 2.5 h.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (1) and step (2), the precursor A and the precursor B are heated to 450-550° C. at a heating rate of 2-10° C. / min for calcination, and the calcination holding time is 2-2.5 hours.
9. A CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8, wherein the mass ratio of CeO2 to ZnMn2O4 is 0.25 to 1:
1.
10. Use of the CeO2 / ZnMn2O4 Z-type heterojunction photocatalyst material according to claim 9 in photocatalytic degradation of tannic acid.
Citation Information
Patent Citations
Catalyst for preparing benzaldehyde through selective oxidation of phenylcarbinol and preparing method thereof
CN105664926A
Efficient flue gas denitration catalyst and preparation method thereof
CN114377688A
ZnMnO3-Mn2O3 / SnO2 composite catalytic material as well as preparation method and application thereof
CN115318279A
Junction material precursor, electrochemical reaction cell stack, and manufacturing method thereof
JP2017188463A